Covalent immobilisation of β-Galactosidase from Escherichia coli to commercially available magnetic nanoparticles for the removal of lactose from milk - Pretorius, Chantelle (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2012.